EFFECT OF PHOTOTHERAPY ON SERUM CALCIUM AND MAGNESIUM LEVELS IN NEWBORNS WITH HYPERBILIRUBINEMIA ADMITTED TO NEONATAL INTENSIVE CARE AT A TERTIARY CARE TEACHING HOSPITAL IN THE KOLHAN REGION OF JHARKHAND - SHYAMLAL MURMU; SIMPAL SHALINI MINJ; RAJAN KUMAR BARNWAL; UMA SHANKER SINGH; KUMAR VIMAL; KUBER CHANDRA SETUA; MANISH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Neonatal jaundice is a medical condition causing yellowish skin discoloration, leading to hospital readmissions in the first 2 weeks of life. It affects 60% of full-term babies and 80% of premature infants. Severe jaundice can cause kernicterus and neurological damage. Treatment options include phototherapy, exchange transfusions, or pharmacological therapy. Phototherapy is the safest and most effective treatment, but it can lead to hypocalcemia and hypomagnesemia due to its effect on the pineal gland. The present study shows the effect of phototherapy on serum calcium and magnesium levels in hyperbilirubinemia. Methods: A prospective observational study was conducted on 221 neonates with hyperbilirubinemia who were treated with phototherapy. We measured bilirubin, calcium, and magnesium levels in their blood samples at admission and 48 h after initiation of phototherapy. The data were analyzed using Epi-Info software. Results: Before phototherapy, the mean serum calcium was 8.79±1.44, but it decreased significantly to 8.13±1.67 (p<0.05). Before phototherapy, the mean serum magnesium level was 3.22±0.72 and reduced considerably to 2.56±0.50 (p<0.05). After phototherapy, total serum bilirubin levels reduced dramatically (from 13.07±3.41 to 8.63±3.10) (p<0.05). Conclusion: The present study shown that phototherapy has a significant effect on the levels of serum calcium, magnesium, and total serum bilirubin by reducing the level.